Research on the Application of Artificial Intelligence and Big Data Technology in Financial Fraud Detection - Wang, Ziyue (Journal of Theory and Practice of Engineering Science, 2024)
Financial fraud is a hidden criminal activity that has a serious impact on the stability of financial markets and investor confidence. Traditional fraud detection methods are often inefficient and unable to meet the rapidly changing fraudulent means. The development of artificial intelligence and big data technology has provided new solutions for financial fraud detection. This article aims to explore the current application status and methods of artificial intelligence and big data technology in financial fraud detection, and analyze the challenges and future development directions.